Self Healing Dan Manajemen Nyeri Persalinan Kala 1 Fase Aktif - Khoirul Waroh, Yuni; Setiawandari, Setiawandari (LPPM - STIKES Pemkab Jombang, 2025)
Childbirth is a very phenomenal event for prospective mothers, where there are very memorable events in their lives, especially related to pain management and anxiety in facing the labor process. Based on a preliminary study of 5 mothers giving birth, it was found that 4 mothers who were going to give birth could not withstand the pain, so the pain became stronger. Self Healing is a way to fight negativity by saying positive affirmation words to the mother so that the mother feels better and more comfortable. This study aims to determine the Effect of Self Healing on the Level of Labor Pain in the First Active Phase of Primigravida at TPMB Naning Widayanti, S.Keb. The type of research is Quasi Experiment with the One Group Pretest-Posttest Design approach. The study population was 37 people, with a sample size of 34 people according to the inclusion criteria. The sampling technique used Acidental Sampling. Before the intervention was given, a pretest was conducted to measure the level of pain using the Numerica Rating Scale, then self-healing intervention was given with positive sentences/affirmations when pain arose for 5 minutes until the opening was 8 cm, then the level of pain was measured again in the post-test. The results of the study obtained before being given Self Healing were that some of the severe pain levels were controlled (47.0%), while after being given Self Healing, some of the mild pain levels were (50%). The results of the Wilcoxon Test p = 0.000, so it was concluded that there was an effect of self-healing on the level of labor pain during the first active phase of primigravida. Suggestions for self-healing therapy can be applied in obstetric services so that it can be used as an alternative complementary obstetric treatment